Respuesta :

Answer:  23) D

                24) 2/3

Step-by-step explanation:

23.

[tex]A) \sqrt{6^2+6^2}=\sqrt{36+36}= \sqrt{72}= 8.5\\\\B) \sqrt{7^2+3^2}=\sqrt{49+9}=\sqrt{58}= 7.6\\\\C) \sqrt{4^2+9^2}=\sqrt{16+81}=\sqrt{97}=9.8\\\\D) \sqrt{15^2-10^2}=\sqrt{225-100}=\sqrt{125}= \large\boxed{11.2}[/tex]

****************************************************************************************

24.

[tex]\sqrt{\bigg(\dfrac{\sqrt2}{3}\bigg)^2+\bigg(\dfrac{\sqrt2}{3}\bigg)^2}=\sqrt{\dfrac{2}{9}+\dfrac{2}{9}}=\sqrt{\dfrac{4}{9}}=\large\boxed{\dfrac{2}{3}}[/tex]

Answer:

23) d. 11.2

24) 2/3

Step-by-step explanation:

I did this question before, so I am just confirming the answer above! ^_^